Bacteriological investigation of pop-eye disease in marine ornamental aquaria fishes from Andaman - Shome, Rajeshwari; Shome, B R; Krishnamurthy, V; Dey, S C; Soundararajan, R (Indian Journal of Fisheries, 2011)
The ornamental marine aquarium fishes suffering from eye disease with symptomsof cataract, exophthalmia, anorexia, dullness and death occurring in 3-5 days wereinvestigated for etiological agent and control measures. The prominent fish speciesaffected were grouper (Epinephelus spp.), Caranx spp., Triacanthus spp., bat fishiPlatax spp.), undulata trigger fish (Balistrapus undulatus), lion fish (.Pterins spp.),vagabond butterfly fish (Chaetndon vagabundus), pearl toby (Canthigasturmargaritata), tang fish (Naso spp.) and snapper (Lutjanus spp,). No parasites werefound to be involved in infected eyes on macroscopic examination. Out of 19representative isolates selected for detailed bacteriological analysis fifteen, threeand one isolates were Vibrio parahaemolyticus. Vibrio anguillarum and Aeromonassalmonicida respectively. The in-vitro antibiotic sensitivity test showed multipledrug resistance against a minimum of five antibiotics to a maximum of thirteenantibiotics. However, norfloxacin and chloramphenicol were found to be effectiveagainst all the bacterial isolates. In isolation, treatment with chloramphenicol @50 mg kg"' body weight when introduced intramuscularly for 5 days was able tocure the disease. As the disease was cured by antibiotics, no parasites could befound on macroscopic examination and 18 out of 19 isolates were found to belongto the genus Vibrio.